Improving Teacher Competence in Developing Love-Based Curriculum Teaching Tools through Artificial Intelligence-Assisted KKG at MIN 2 North Halmahera - Adiyana Adam; Rosdiana Im; Kartini Limatahu; Irma Sapsuha; Azis Los'en; Erina Junaedi; Kamarun M Sebe (Socio-Economic and Humanistic Aspects for Township and Industry, 2026)
This study aims to analyze the improvement of teachers' competence in developing teaching materials for the Love-Based Curriculum through the activities of the Teacher Working Group assisted by Artificial Intelligence at MIN 2 North Halmahera. The study used a Classroom Action Research approach with a two-cycle design that includes the stages of planning, action implementation, observation, and reflection. Cycle I was positioned as a discovery mission to identify teachers' initial understanding and challenges in implementing the Love-Based Curriculum, while Cycle II functioned as an action change designed based on the results of the previous cycle's reflection. Data collection techniques included observation, interviews, and document analysis of teachers' teaching materials. Data were analyzed qualitatively through the processes of reduction, presentation, and drawing conclusions. The results showed that the activities of the Teacher Working Group assisted by Artificial Intelligence were able to significantly improve teachers' pedagogical competence. This improvement was evident in the shift in the practice of preparing teaching materials from administrative and declarative to a more operational, reflective learning design, and oriented towards the internalization of human values. Teachers demonstrated better abilities in integrating learning objectives, reflective activities, and holistic assessments in accordance with the principles of the Love-Based Curriculum. In addition, Artificial Intelligence was utilized more critically as a cognitive partner in learning planning. This study concludes that the synergy between the Love-Based Curriculum value framework, the teacher professional community, and the use of artificial intelligence technology plays a crucial role in teacher professional development in madrasah.